Stock Market in Times of Current Crises - Kříž, Matyáš (2023)
Diploma thesis focuses on the impacts of current crises on the stock market. It utilizes an event study methodology with the market model to analyze impacts of the Covid-19 pandemic and the Russian invasion into Ukraine on benchmark indices of thirty of the largest economies around the world. Additionally, it identified the impacts on ten different industries through sector indices divided according to the GICS methodology. In total the impacts of eight event are analysed in the thesis, four for each of the crises. Overall, for five out of eight events statistically significant impact are identified visible on the cumulative abnormal returns. The thesis also shows the limitations of using the market model for analysing impacts of events of such global significance as the Covid-19 pandemic.